2020
DOI: 10.1177/1179546820955179
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Association Between Inflammatory Bowel Disease and Cardiac Arrhythmias: An Examination of the United States National Inpatient Sample Database

Abstract: Background: Inflammatory bowel diseases (IBD) associated-chronic inflammation and autonomic dysregulation may predispose to arrhythmias. However, its exact prevalence is unknown. Thus, we aimed to ascertain the prevalence of arrhythmias in patients with IBD. Methods: We queried the Nationwide Inpatient Sample (the largest publicly available all-payer inpatient USA database) from 2012 to 2014. We used the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9 CM) discharge codes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…15 Most studies have noted a female and Caucasian predominance in this patient population. 16,17 In our study, the prevalence and mean age for IBD hospitalizations with AF was noted to be 4.2% (3900 patients) and 70.9 years, respectively. These findings were in line with current literature.…”
Section: Discussionmentioning
confidence: 47%
“…15 Most studies have noted a female and Caucasian predominance in this patient population. 16,17 In our study, the prevalence and mean age for IBD hospitalizations with AF was noted to be 4.2% (3900 patients) and 70.9 years, respectively. These findings were in line with current literature.…”
Section: Discussionmentioning
confidence: 47%
“…During the follow-up of a population-based cohort study, patients with IBD were identified at a 36% (95% CI, 20–54%) higher risk of AF than controls ( 6 ). On the contrary, using the nationwide inpatient database in the United States, patients with IBD were found less likely to be hospitalized for arrhythmias than the non-IBD (9.7 vs. 14.2%, p < 0.001) ( 7 ). The potential biases of confounding factors and reverse causation may contribute to such controversy ( 8 ), leaving the specific relationship between IBD and AF yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, hospital characteristics were incorporated into the analysis (hospital region, hospital bed size, location, and teaching status). The NIS database has been previously used to successfully identify the impact of IBD on different groups of patients [ 17 ].…”
Section: Methodsmentioning
confidence: 99%